Surgeons’ awareness about ergonomics in the operation theatre - Masab Nawaz; S H Waqar; Zakir Jamal; Fatima Shahzad (Journal of Shalamar Medical & Dental College)
Background: Musculoskeletal symptoms are common among surgeons who work in an environment that is not ergonomically ideal.